ANALYSIS OF THE EFFECTIVENESS, USABILITY, AND SAFETY ASPECTS OF MARINE WASTE CRAFT PRODUCTION MACHINES ON THE PRODUCTIVITY OF COASTAL COMMUNITIES IN BATAM CITY - Arina Luthfini Lubis; Frangky Silitonga; Putri Sima Siallagan (RADJA PUBLIKA, 2025)
This study is motivated by the low productivity of coastal communities in processing marine waste into economically valuable handicrafts. One of the main obstacles is the lack of proper production tools, which results in inefficient and time-consuming work processes. The purpose of this research is to analyse the effect of production machine effectiveness on increasing the productivity of coastal communities in Batam City. The study adopts a quantitative approach with a descriptive-associative design. Data were collected from 30 respondents using a Likert-scale questionnaire and analysed through validity and reliability tests, multiple linear regression, and classical assumption tests. The results show that the variables of effectiveness, ease of use, and work safety have a significant simultaneous effect on productivity. The regression model formed is: Y = 32.911 – 0.520X₁ + 0.291X₂ – 0.417X₃, with an adjusted R square value of 0.655. This indicates that 65.5% of the variation in community productivity can be explained by the three variables. This research confirms that the use of production machines can serve as a strategic solution to improve work efficiency and productivity among coastal communities. These findings are expected to serve as a foundation for developing future community empowerment programs based on appropriate technology.